Intensive lipid lowering agents and coronary atherosclerosis: Insights from intravascular imaging - Giuseppe Di Giovanni; Stephen J Nicholls (Elsevier, 2022)
Advances in intravascular imaging have permitted comprehensive evaluation of coronary atherosclerotic plaque from the perspective of its burden and individual components. These advances have been integrated in clinical trials that have evaluated the impact of intensive lipid lowering regimens. These trials have demonstrated that intensive lipid lowering, using high dose statins as monotherapy and in combination with new lipid lowering agents, produce favorable effects on coronary atheroma, resulting in regression and stabilization. These findings provide important biological insights to understand how intensive lipid lowering may reduce cardiovascular risk. This review aims to provide the reader with a contemporary overview of the findings of these studies and to propose the potential clinical implications for management of higher risk patients with atherosclerotic coronary artery disease.